Effects of obstructive sleep apnoea risk on postoperative respiratory complications: protocol for a hospital-based registry study. Issue 1 (13th January 2016) - Shin, Christina H; Zaremba, Sebastian; Devine, Scott; Nikolov, Milcho; Kurth, Tobias; Eikermann, Matthias
Abstract : Introduction: Obstructive sleep apnoea (OSA), the most common type of sleep-disordered breathing, is associated with significant immediate and long-term morbidity, including fragmented sleep and impaired daytime functioning, as well as more severe consequences, such as hypertension, impaired cognitive function and reduced quality of life. Perioperatively, OSA occurs frequently as a consequence of pre-existing vulnerability, surgery and drug effects. The impact of OSA on postoperative respiratory complications (PRCs) needs to be better characterised. As OSA is associated with significant comorbidities, such as obesity, pulmonary hypertension, myocardial infarction and stroke, it is unclear whether OSA or its comorbidities are the mechanism of PRCs. This project aims to (1) develop a novel prediction score identifying surgical patients at high risk of OSA, (2) evaluate the association of OSA risk on PRCs and (3) evaluate if pharmacological agents used during surgery modify this association. Methods: Retrospective cohort study using hospital-based electronic patient data and perioperative data on medications administered and vital signs. We will use data from Partners Healthcare clinical databases, Boston, Massachusetts. First, a prediction model for OSA will be developed using OSA diagnostic codes and polysomnography procedural codes as the reference standard, and will be validated by medical record review. Results of the prediction model will be used to classify patients in the database as high, medium or low risk of OSA, and we will investigate the effect of OSA on risk of PRCs. Finally, we will test whether the effect of OSA on PRCs is modified by the use of intraoperative pharmacological agents known to increase upper airway instability, including neuromuscular blockade, neostigmine, opioids, anaesthetics and sedatives. Ethics and dissemination: The Partners Human Research Committee approved this study (protocol number: 2014P000218). Study results will be made available in the form of manuscripts for publication and presentations at national and international meetings.